2017
DOI: 10.15421/nvlvet7826
|View full text |Cite
|
Sign up to set email alerts
|

Характеристика Морфологічних Ознак Та Фізіологічних Властивостей Штамів Сальмонел, Ізольованих Від Птиці І Телят

Abstract: In order to develop effective domestic drugs for the prevention of animal salmonella, in our previous studies, 30 isolates of salmonella were obtained from different collections, including those isolated from epizootic centers of salmonellosis. From this collection, six strains of salmonella were selected as promising production strains for constructing vaccine preparations against salmonellosis and as controls for the study of the immunogenic properties of vaccines.The article presents the results of comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…It has been found that avian salmonellosis vaccines should contain protective antigens that would stimulate the formation of protective antibodies against the above-mentioned salmonella serotypes (Trockyi, 2012). There were also found patterns in the manifestation of virulence and antigenic properties of the studied strains of Salmonella, namely, the higher the virulence of the strain, the higher its antigenic activity (Boiko et al, 2017). To develop vaccines against salmonellosis of poultry, socially important strains of Salmonella which most often cause food poisoning are chosen, such as S. typhimurium, S. enteritidis and S. gallinarum (Nair et al, 2018;Cao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that avian salmonellosis vaccines should contain protective antigens that would stimulate the formation of protective antibodies against the above-mentioned salmonella serotypes (Trockyi, 2012). There were also found patterns in the manifestation of virulence and antigenic properties of the studied strains of Salmonella, namely, the higher the virulence of the strain, the higher its antigenic activity (Boiko et al, 2017). To develop vaccines against salmonellosis of poultry, socially important strains of Salmonella which most often cause food poisoning are chosen, such as S. typhimurium, S. enteritidis and S. gallinarum (Nair et al, 2018;Cao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Зважаючи на це, нами підібрано виробничоконтрольні штами сальмонел (Boiko et al, 2017), розроблено і запропоновано низку вакцинних препаратів (моно-, бі-і тривалентних, водних і емульсованих), в результаті яких було встановлено, що найефективнішою проти сальмонельозу птиці виявилася бівалентна інактивована емульсована вакцина, виготовлена із S. typhimurium і S. enteritidis -штамів, які були виділені від птиці і виявили високі антигенні та проективні властивості . Вакцина пройшла відповідні лабораторні випробування за показниками безпеки та якості.…”
Section: результати та їх обговоренняunclassified
“…В більшості випадків в їхній основі лежать інфекційні захворювання переважно бактерійного походження. Водночас існує багато факторів як біотичних, так і абіотичних, які виступають пусковим механізмом та значно впливають на подальший розвиток цих захворювань, а також ефективність методів та засобів їх профілактики і лікування (Kurtyak et al, 2017;Boiko et al, 2017;Levkivska et al, 2017;Kysera et al, 2018;Gutyj et al, 2018).…”
Section: вступunclassified